Primary sclerosing cholangitis. - Cullen, S; Chapman, R (2003)
Primary sclerosing cholangitis (PSC) is a fibrosing disease of the intra- and extra-hepatic bile ducts, and is closely associated with inflammatory bowel disease. It is immune mediated, rather than being a classical autoimmune disease. A range of immune abnormalities have been demonstrated in PSC, in particular the findings of a range of autoantibodies, a portal tract infiltrate of functional T cells, a restricted T-cell receptor repertoire, and aberrant expression of HLA molecules on biliary epithelial cells. The immunogenetics of PSC is currently under study and to date 4 key HLA haplotypes associated with PSC have been developed. The trigger factor for the initiation of the immune response may be the ingress of bacteria or other toxic metabolites into the portal circulation through a diseased and permeable bowel wall.